Extruded flakes from pearl millet (Pennisetum glaucum)-carrot (Daucus carota) blended flours-production, nutritional and sensory attributes - Adebanjo, L.A.; Olatunde, G.O.; Adegunwa, M.O.; Dada, O.C.; Alamu, Emmanuel Oladeji (Informa UK Limited, 2020)
Millet flour (M) and carrot flour(C) were produced and blended in the ratios 100M:0C, 95M:5C, 90M:10C, 85M:15C and 80M:20C respectively to produce extruded flakes. The composite flours were subjected to analysis of the proximate and mineral composition, as well as functional and pasting properties. Extruded flakes were analyzed for proximate composition, total carotenoids, colour and sensory evaluation. There was no significant difference (p > 0.05) in the proximate, functional and pasting properties but there were significant differences (p < 0.05) in the mineral composition (Ca, Fe, Zn, Mg and P). Extrusion cooking significantly (p < 0.05) reduced moisture content from 4.5 to 3.5%, and it is also significantly (p < 0.05) increased the crude fibre from 2.84 to 4.53%, on the other hand, protein content decreased with the increase in carrot flour. Total carotenoids were not significantly (p > 0.05) affected by extrusion cooking. In terms of the lightness (L*), redness (a*) and yellowness (b*), 100% millet flakes had the least values of 50.09, 0.076 and 10.39 respectively. Sample with 85M:15C had the overall acceptance score of 7.25. In terms of colour and taste, the sample with 90M:10C had the highest scores of 8.50 and 6.50 respectively. Sample with 85M: 15C was most preferred in terms of crunchiness. The results indicate that pearl millet and carrot are rich in different nutrient when blended in the right proportions to make composite flour, it would produce nutrient-dense food product rich in protein, vitamin Aand minerals.